Amphibian (Xenopus laevis) Tadpoles and Adult Frogs Differ in Their Antiviral Responses to Intestinal Frog Virus 3 Infections - Hauser, Kelsey A.; Singer, Julia C.; Hossainey, Muhammad Riadul H.; Moore, Tyler E.; Wendel, Emily S.; Yaparla, Amulya; Kalia, Namarta; Grayfer, Leon (Frontiers in Immunology, 2021)
The global amphibian declines are compounded by ranavirus infections such as Frog Virus 3 (FV3), and amphibian tadpoles more frequently succumb to these pathogens than adult animals. Amphibian gastrointestinal tracts represent a major route of ranavirus entry, and viral pathogenesis often leads to hemorrhaging and necrosis within this tissue. Alas, the differences between tadpole and adult amphibian immune responses to intestinal ranavirus infections remain poorly defined. As interferon (IFN) cytokine responses represent a cornerstone of vertebrate antiviral immunity, it is pertinent that the tadpoles and adults of the anuran Xenopus laevis frog mount disparate IFN responses to FV3 infections. Presently, we compared the tadpole and adult X. laevis responses to intestinal FV3 infections. Our results indicate that FV3-challenged tadpoles mount more robust intestinal type I and III IFN responses than adult frogs. These tadpole antiviral responses appear to be mediated by myeloid cells, which are recruited into tadpole intestines in response to FV3 infections. Conversely, myeloid cells bearing similar cytology already reside within the intestines of healthy (uninfected) adult frogs, possibly accounting for some of the anti-FV3 resistance of these animals. Further insight into the differences between tadpole and adult frog responses to ranaviral infections is critical to understanding the facets of susceptibility and resistance to these pathogens.